Innovation in Virtual Learning Based on Teaching Factory on Robotic Welding in Vocational Education: A Systematic Literature Review - Herianto Herianto; Aditia Gustiana Gunawan; R. Machmud Sugandi (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2026)
The rapid adoption of automation and robotics in manufacturing has intensified the need for vocational graduates with integrated digital, systems-thinking, and advanced welding competencies. Despite growing interest in virtual learning and Teaching Factory (TeFa) models, research on their application in robotic welding education remains fragmented. This study synthesizes existing evidence on virtual Teaching Factory innovations for robotic welding in vocational education through a Systematic Literature Review conducted in accordance with PRISMA 2020 guidelines. Peer-reviewed journal articles and conference proceedings published between 2013 and 2024 were retrieved from Scopus, Web of Science, IEEE Xplore, ScienceDirect, and ERIC. Following rigorous inclusion and exclusion criteria, twenty studies were analyzed using thematic synthesis. The findings reveal that immersive technologies, particularly virtual reality, welding simulation, and augmented training environments, have demonstrated positive effects on practice-based learning outcomes. Influence learners’ cognitive and psychomotor skill development, motivation, and operational safety. However, virtual learning is predominantly implemented as a supplementary tool rather than as an integrated Teaching Factory system. Hybrid learning configurations that combine virtual and physical environments demonstrate the strongest potential for enhancing industrial relevance and systems-level understanding. This review contributes a reminder conceptual synthesis of virtual Teaching Factory applications in robotic welding and identifies critical gaps for future research, emphasizing the need for longitudinal, pedagogy-driven, and industry-validated studies to advance vocational education in Industry 4.0 contexts.